Суспільно-політичні рухи у південноукраїнському регіоні на початку ХХ ст. (Zaporizhzhia Historical Review, 2021)
The social and political movement of Southern Ukraine is considered and analyzed as certain territorial integrity. Author marked out four directions in the social and political movement: Ukrainian national movement; allimperial movements; national minority's movement; territorial (regional) tends. Author proved that only complex approach is appropriate to researching of social and political life of Southern Ukraine region. It's impotent to author's mind to take proper account of interference of those social and political directions (and organizations, which represented them) in social and political movements.